Major Crop Species Show Differential Balance between Root Morphological and Physiological Responses to Variable Phosphorus Supply - Lyu, Yang; Tang, Hongliang; Li, Haigang; Zhang, Fusuo; Rengel, Zed; Whalley, William R.; Shen, Jianbo (Frontiers in plant science, 2016)
The relationship between root morphological and physiological responses to variable P supply in different plant species is poorly understood. We compared root morphological and physiological responses to P supply in seven crop species ( , , , , ) treated with or without 100 mg P kg in two soils (acidic and calcareous). Phosphorus deficiency decreased root length more in fibrous root species ( ) than legumes. and had higher root/shoot biomass ratio and had higher specific root length compared to legumes, whereas legumes (except soybean) had higher carboxylate exudation than fibrous root species. exhibited the highest P-acquisition efficiency due to high exudation of carboxylates and acid phosphatases. and depended mostly on root exudation (i.e., physiological response) to enhance P acquisition, whereas had higher root morphology dependence, with and in between. Principal component analysis using six morphological and six physiological responses identified root size and diameter as the most important morphological traits, whereas important physiological responses included carboxylate exudation, and P-acquisition and P-utilization efficiency followed by rhizosphere soil pH and acid phosphatase activity. In conclusion, plant species can be grouped on the basis of their response to soil P being primarily via root architectural or exudation plasticity, suggesting a potential benefit of crop-specific root-trait-based management to cope with variable soil P supply in sustainable grain production.